1999
DOI: 10.1002/(sici)1099-1263(199912)19:1+<s59::aid-jat617>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of reactive topical skin protectants against sulfur mustard and nerve agents

Abstract: The potential for highly reactive nanoparticles (RNP) to absorb destructively, i.e. to neutralize highly toxic substances such as the warfare agents GA, GB, HD and VX, has been demonstrated in the laboratory. Reactive nanoparticles represent a new class of nanoscale particles of metals and metal oxides that differ from other nanoparticles in reactivity and crystalline morphology. The potential for incorporating RNP into a protective barrier skin cream also has been demonstrated. Preliminary studies indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 2 publications
(2 reference statements)
1
19
0
Order By: Relevance
“…According to Talmage et al [9], and Devereaux et al [10], CEES molecule acts as cytotoxin or mutatoxin via an intermediate form that binds to DNA, particularly in the bone marrow leading to blood disorders [11], Vorontsov et al [12], advanced that high toxicity of these molecules is also associated with the ability of the SCH2CH2Cl group to alkylate proteins.…”
Section: Introductionsupporting
confidence: 88%
“…According to Talmage et al [9], and Devereaux et al [10], CEES molecule acts as cytotoxin or mutatoxin via an intermediate form that binds to DNA, particularly in the bone marrow leading to blood disorders [11], Vorontsov et al [12], advanced that high toxicity of these molecules is also associated with the ability of the SCH2CH2Cl group to alkylate proteins.…”
Section: Introductionsupporting
confidence: 88%
“…The subsequent step was to assess whether DSM was an appropriate VX surrogate ) as compared to POX which, like parathion, demethon-S, N,N-diisopropyl-2-aminoethyl-p-fluorobenzene thiosulfonate and tetriso, have already been used as simulant of V agents (Koper et al, 1999;Wester et al, 2000;Fischer et al, 2005;Cassagne et al, 2001;Hoskin et al, 1995). To that end, we compared the present percutaneous penetration profiles and toxico-kinetic parameters of VXeq through ST, FT pig-ear or human abdominal skin samples (Table 2, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While paraoxon (POX), parathion, demethon-S and tetriso, have already been used as VX simulants (Koper et al, 1999;Wester et al, 2000;Fischer et al, 2005;Hoskin et al, 1995), demeton-Smethyl (DSM) may provide a suitable surrogate due to physicochemical properties akin to VX such as: phosphor-sulfur bonds, molecular weight, volatility and liphophilic/hydrophilic feature.…”
Section: Introductionmentioning
confidence: 99%
“…2-CEPS and 2-CEES could act as cytotoxin or mutatoxin via an intermediate form that facilitate their binding to DNA, especially in the bone marrow [6]. Particularly, this would lead to aplastic anemia (decrease in blood cells) or pancytopenia (red and white blood cells and platelets) [7]. Vorontsov et al [8] suggested that high toxicity of this molecule is also associated with the ability of the SCH 2 CH 2 Cl group to alkylate proteins.…”
Section: Introductionmentioning
confidence: 99%